Emerging micropollutants: risks, regulatory trends, and adsorption based-magnetic nanotechnology solutions - Mumtaz, Amina; Santini, Saul; Albino, Martin; Muzzi, Beatrice; Marinelli, Cristian; Cincinelli, Alessandra; Sangregorio, Claudio; Martellini, Tania (Frontiers in Environmental Chemistry, 2026)
Emerging micropollutants (EMPs) like pharmaceuticals, personal care products, pesticides, microplastics, flame retardants and per- and polyfluoroalkyl substances (PFAS), are a growing concern in aquatic environments due to their persistence, bioaccumulation, and potential toxicity. While traditional wastewater treatment technologies like advanced oxidation processes and microbial degradation may be efficient, they tend to be expensive, sophisticated, and inadequate in fully eliminating EMPs. Adsorption via metallic and metal oxide nanomaterials offers an attractive, low-cost and effective option over traditional technologies. This review focuses on various EMPs, pesticides among them, and their adverse impacts. It presents the physical and chemical adsorption processes employed by metal and metal oxide nanomaterials for the removal of these contaminants. Various synthesis techniques of such nanoparticles from chemical, physical, and biological techniques are discussed, highlighting their respective merits and drawbacks. The role of nanomaterials in wastewater treatment, particularly in the removal of heavy metals, antibiotics, and pesticides, is highlighted due to their high adsorption efficiency. The review also discusses the importance of nanoparticle recovery and regeneration to promote green and sustainable water treatment systems. In conclusion, it demonstrates that although nanotechnology offers significant promise for addressing water pollution, more research is needed into eco-friendly synthesis methods to improve its effectiveness in environmental remediation.